The Role of Leadership in Library Digitalization: How Digital Technology Innovation in Enhancing Cognitive and Literacy Development in Local Communities - Idris, Julizar (Faculty of Law, Universitas Pekalongan, 2024)
This study investigates the impact of leadership and library digitalization on cognitive and literacy levels within diverse communities across nine regions in Indonesia. Study aims to examines how visionary leadership, strategic planning, stakeholder engagement, and resource allocation by government representatives, along with the managerial effectiveness and innovation practices of librarians, influence library services' modernization and community literacy. Mixed-methods approach were employed, including qualitative and quantitative data which were collected to evaluate the relationship between leadership effectiveness and digital library implementation. Findings reveal that strong leadership and strategic resource allocation are critical in overcoming barriers to library digitalization, fostering digital literacy, and improving community access to knowledge. Data highlights the role of feedback-driven user-centric approaches and training programs in equipping librarians with the skills required for effective service delivery. The insights derived contribute to understanding the dynamics of leadership in advancing digital library initiatives, offering practical recommendations for policymakers and librarians aiming to bridge literacy gaps in the digital age.